Table of Content - - (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content: 1. The future roles of school principals in light of the trend towards a knowledge society Ms. Rimah Mudawi Mansour 2. The tracking of the development and spread of Covid 19 pandemic in the territory of the Taza Province / Morocco Dr. Abdelouahed Bouberria, Dr. Abdelhafid Hammimi, Dr. Mohammed Abahrour, Dr. Mohammed Errafik 3. The Impact of Advertising Campaigns on Consumers’ Purchasing Decision in Delivery Application A Field Study on Grocery Delivery App in Saudi Arabia Ms. Wasaef Ali Bakhashwain, Ms. Lara Zainalabdien Serri, Co-Prof. Mohamed Gad Elmawla Owies 4. The Relation of Governance Principles with Job Satisfaction with the Employees of the Ministry of Education, Sultanate of Oman Dr. Mouza Said Al-Kharusi 5. The emergence of modern intellectual Currents: The Aqeeqah feast between the permissible and the forbidden in northern Togo “Cinkasse” Mr. Ibrahim Youssif